Rosai-Dorfman Disease: Self-Resolving Unilateral Lymphadenopathy and a Brief Review of Literature - Joshua Feriante; Richard T. Lee (Case Reports in Oncological Medicine)
Rosai-Dorfman disease (RDD), also known as sinus histiocytosis with massive lymphadenopathy (SHML), is a disease of histiocytic proliferation with no known pathogenesis. This disease is defined by histological and cytological characteristics, including emperipolesis and positive S100 and CD68 markers. Although the disease typically presents clinically with massive bilateral lymphadenopathy due to sinus expansion from excessive histiocytosis, only unilateral lymphadenopathy was observed in this patient. The case involves a 40-year-old Caucasian male from the Netherlands presenting with unilateral lymphadenopathy suspicious for malignancy. Subsequent histological and laboratory testing led to the rare diagnosis of RDD. The lymphadenopathy resolved spontaneously over the course of several weeks following the initial presentation. Rosai-Dorfman disease reportedly has a benign prognosis with approximately 20% of patients experiencing spontaneous disease resolution (as was the case for this patient) with 70% experiencing chronic symptoms that may last years but not require intervention. We therefore advocate observation as a mainstay of treatment for most cases of this rare disease with intervention only being pursued in symptomatic cases. A review of recent literature regarding pathogenesis, epidemiology, diagnostic factors, prognosis, and treatment is provided and discussed.